2015
DOI: 10.1177/0894845314568190
|View full text |Cite
|
Sign up to set email alerts
|

Developing Attitudes Toward an Entrepreneurial Career Through Mentoring

Abstract: Mentoring is reputed to support the career choices and development of individuals in various contexts. This study is one of the few that investigates the effect of mentoring on career satisfaction and retention of novice entrepreneurs. We surveyed 360 novice entrepreneurs who had been supported by a mentor. Our analyses demonstrate the direct effect of mentoring on entrepreneurial self-efficacy, which mediates the relationship between satisfaction of being an entrepreneur and the intention of staying in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 54 publications
6
62
0
3
Order By: Relevance
“…Another approach to increasing ESE is through mentoring. In their study of 360 novice entrepreneurs, St-Jean and Mathieu [19] found that mentoring had a direct effect on ESE, mediating the relationship between satisfaction and intention to stay in the profession; furthermore, St-Jean [18] found that mentoring "maximizes the learning" for novice entrepreneurs, primarily through career-related mentoring functions.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to increasing ESE is through mentoring. In their study of 360 novice entrepreneurs, St-Jean and Mathieu [19] found that mentoring had a direct effect on ESE, mediating the relationship between satisfaction and intention to stay in the profession; furthermore, St-Jean [18] found that mentoring "maximizes the learning" for novice entrepreneurs, primarily through career-related mentoring functions.…”
Section: Introductionmentioning
confidence: 99%
“…It is about helping people to make their own choices, thus it is not dictating what to do or how to do (Kay and Hinds,2009:5). It is a form of practice that makes people questioning what, how, why, when and with whom they are doing, therefore allow people to make informed choices and persevere when faced with difficulties (St-Jean and Mathieu, 2015). As the important training and development tool for upward progression, mentoring is not a new concept (Hunt and Micheal,1983).…”
Section: Garden Of Mentoring: Brief Discussion About Definitional Issmentioning
confidence: 99%
“…They are also skilled at resolving personal and professional dilemmas by provoking self-questioning (St-Jean and Mathieu,2015). Despite their important functions in entrepreneurial process, their multi-faceted development effect for new-start entrepreneurs or mentee/protégé is not highly discussed topic in the entrepreneurship literature to the best of our knowledge (St-Jean and Mathieu, 2015;St-Jean and Audet,2009). However, mentoring programs provided under both several private and public initiatives are increasingly on the agenda of fostering entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fayolle et al (2006) have stated that EI becomes stronger when self-efficacy is enhanced by the presence of ERMs. St-Jean and Mathieu (2015), however, observed that mentoring appears to have a direct negative effect on the intension (to stay in the profession) of novice entrepreneurs; and suggested that mentoring should come earlier in the entrepreneurial process.…”
Section: Comparison Of Categorical Effects Of Perms and Nermsmentioning
confidence: 97%